A lower eyelid and cheek defect reconstruction - Vittoria Cioppa; Pietro Rubegni; Ernesto De Piano (PAGEPress Publications, 2023)
A 91 years old woman presented with a recurrent cutaneous squamous cell carcinoma (CSCC) involving the right lower eyelid and cheek. Recurrence occurred after one month from an incomplete surgical excision: histology reported a tumor infiltration of the subcutaneous tissue and deep margin. [...]